Ocena częstości występowania stresu, objawów mu towarzyszących, przyczyn oraz sposobów radzenia sobie w sytuacjach stresowych wśród osób uczących się = Estimation of the frequency of occurrence of stress and its symptoms and evaluation of causes and management of stress among students / learners - Kozłowski, Piotr; Kożuch, Katarzyna; Kozłowska, Magdalena; Cuch, Barbara; Kozłowska, Karolina (Journal of Education, Health and Sport, 2016)
Kozłowski Piotr, Kożuch Katarzyna, Kozłowska Magdalena, Cuch Barbara, Kozłowska Karolina. Ocena częstości występowania stresu, objawów mu towarzyszących, przyczyn oraz sposobów radzenia sobie w sytuacjach stresowych wśród osób uczących się = Estimation of the frequency of occurrence of stress and its symptoms and evaluation of causes and management of stress among students / learners. Journal of Education, Health and Sport. 2016;6(5):393-402. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.53170 http://ojs.ukw.edu.pl/index.php/johs/article/view/3531 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. Ocena częstości występowania stresu, objawów mu towarzyszących, przyczyn oraz sposobów radzenia sobie w sytuacjach stresowych wśród osób uczących się Estimation of the frequency of occurrence of stress and its symptoms and evaluation of causes and management of stress among students / learners Piotr Kozłowski1, Katarzyna Kożuch2, Magdalena Kozłowska3, Barbara Cuch1, Karolina Kozłowska4 1Katedra Anatomii Człowieka, Zakład Anatomii Prawidłowej, UM w Lublinie 2Uniwersytet Medyczny w Lublinie 3Katedra i Klinika Neurologii, UM w Lublinie 4Instytut Filologii Angielskiej, KUL w Lublinie Uniwersytet Medyczny w Lublinie ul. W. Chodźki 1, 20-093 Lublin e-mail: piotr7176@gmail.com Streszczenie Celem pracy była ocena częstości występowania stresu, przyczyny oraz sposoby radzenia sobie w sytuacjach trudnych wśród osób uczących się. Badaniem objęto 102 osoby. Kobiety stanowiły 57,8% respondentów, natomiast mężczyźni 42,2%. Wiek ankietowanych zawierał się w przedziale od 18 do 30 lat. Badanie przeprowadzono w okresie od września do października 2015 roku metodą wywiadu standaryzowanego. Narzędziem użytym do zebrania danych, był autorski, anonimowy kwestionariusz. Kwestionariusz zawierał 25 pytań z możliwością jednokrotnego wyboru w tym trzy pytania z możliwością wielokrotnego wyboru. Przeprowadzono analizę statystyczną z wykorzystaniem testu chi- kwadrat. Wszystkie wartości w których p<0,05 uznano za istotne statystycznie. Wśród ankietowanych niespełna połowa (47,1%) znajdowała się w sytuacji stresowej kilka razy w tygodniu. Natomiast stres odczuwało kilka razy dziennie aż 21,6% ankietowanych. Respondenci to osoby młode, kształcące się to też jako główny powód stresu wskazany został związek ze szkołą bądź studiami (74,5%). Problemy rodzinne wywołują stres u 59,8%. Wśród objawów stresu ankietowani wskazywali rozdrażnienie, gniew, ból brzucha, uczucie bezradności, problemy z koncentracją oraz zaburzenia łaknienia. Blisko połowa ankietowanych (47,5%) deklaruje, że po przejściu okresu stresu objawy z nim związane mijają. Nie ma istotnych statystycznie różnic dotyczących długości występowania objawów biorąc pod uwagę płeć. Najskuteczniejszą metodą radzenia sobie ze stresem jest wsparcie drugiej osoby, odpowiedź tą wybrała prawie polowa respondentów (49,5%). Większość ankietowanych (62,4%) dzieli się swoimi problemami z rodziną i bliskimi. Mężczyźni istotnie statystycznie (p<0,05) częściej nie mówią o swoich problemach z bliskimi. Słowa kluczowe: stres, sytuacja stresowa, przyczyny stresu, sposoby radzenia sobie ze stresem. Abstract The aim of the study was to evaluate the frequency of the occurrence of stress, as well as causes and ways of coping with difficult situations. The study involved 102 learners. Women accounted for 57.8% of the respondents, men- 42.2%. The age of respondents ranged from 18 to 30 years. The study was conducted between September and October 2015. The research method employed was a standardized interview. The tool used for data collection was an anonymous questionnaire. The questionnaire contained 25 single-choice, and three multiple-choice questions. Statistical analysis was performed using chi-square test. All values in which p <0.05 was considered statistically significant. Among those surveyed less than a half (47.1%) was in a stressful situation a couple of times a week. While up to 21.6% of the respondents were affected by stress up to several times a day. The respondents were young people who actively studied, and therefore situations related to exams and attending classes were for the majority of the respondents (74.5%) the main cause of stress. In 59.8% stress occurred because of family-related or personal problems. Among the symptoms of stress, respondents pointed out: irritability, anger, abdominal pain, feeling of helplessness, problems with concentration and appetite disorders. Nearly half of the respondents (47.5%) claimed that whenever the stressful period or situation passes, the symptoms associated with it also disappear. Thaking into account the gender of the respondents, there are no statistically significant differences in the duration of the symptoms. Almost half of the respondents (49.5%), stated that the most effective method of dealing with stress is other person’s support. The majority of the respondents (62.4%) admitted to sharing their problems with their families and loved ones. Male respondents whose answers were statistically significant (p <0.05) were more likely to not talk about their problems with their loved ones. Key words: stress, stressful situations, the causes of stress, ways of coping with stress.